Evaluación de diferentes dosis de moringa (Moringa oleífera) como promotor de crecimiento y acabado de pollos broiler en la provincia Bolívar - Díaz Sánchez, Katherinne Sthefanny (2019)
The evaluation of different doses of moringa (Moringa oleífera) as promoter of growth and finishing of broiler chickens, was carried out in Bolívar Province, Guaranda Canton, Sector Laguacoto II, the objectives of the investigation were: To evaluate the different moringa doses (Moringa oleifera) as a promoter in the growth and finishing of chicken broilers; To establish the optimum dose 0, 50gr / ton, 100gr / ton, 150gr / ton, 200gr / ton, of moringa in the feeding of chickens; Perform the bromatological analysis of Moringa oleifera; Determine the economic profitability in relation to benefit / cost. The block design was used completely at random, with the Moringa oleifera study factors at a dose of 50gr / ton, 100gr / ton, 150gr / ton, 200gr / ton, compared to the control in the diet of 300 broiler chickens, in the results can be noted that the addition of Moringa oleifera in the diet of broiler chickens, if it contributed positive effects in the production, giving poultry farmers alternatives to supplement the diets of the chickens, since better results were obtained in the proposed variables , based on these results it is recommended to use Moringa oleifera at a dose of 200gr / ton in broiler chicken diet (T5) since average weights of 2696.72 grams were obtained per bird at the sixth week, compared to the (T1) obtained average results of 2287.56 grams per bird at the sixth week, with T5 being the best results in the present investigation.